Caracterización de los residuos sólidos domiciliarios generados en el centro poblado Barrio Florido, Punchana, 2022 - Vigo Gonzales, Teresa De Jesus (2022)
The present work of thesis was developed in the Village of Barrio Florido situated on the left side of the amazon river to 45 minutes from the city of Iquitos, the evaluation was realized during the months of December 2021 to March 2022, and it had had as objective realize the characterization of the household solid waste generated in the Village Barrio Florido; as well as, develop the quantification of the waste, calculate the density and determinate the per capita generation; also, it had registered the opinion of the people whose live in the Village Barrio Florido about the generation, segregation and disposition of the household solid waste of its community. Whit the propose of to know about the amount and types of the household solid waste to improve its segregation and disposition. Through the analysis and the processing of the information collected from the population of the Village Barrio Florido, it had obtained from the quantification of the waste a total value of 4224.000 kg, been the organic waste, the mayor waste generated with a value of 1883.430 kg, followed of plastic with 1273.390 kg, paper with 430.880 kg, paperboard with 425.680 kg, metal with 181.220 kg and glass with 29.400 kg.